Experimental and numerical evaluation of friction behaviour between hardwood timber and brick masonry in earth mortar: cyclic triplet shear test and pull-out test - Yohei Endo; Y. Waki; T. Goda (Discover Applied Sciences)
Abstract Brick masonry in earth mortar is a traditional construction technique still used in South and Southeast Asia. Timber beams and columns are often taken advantage of to improve the seismic performance of such structures. Nonetheless, the contribution of these timber elements has not been fully understood yet partially due to the complex friction behaviour between timber and masonry. In the present research, a cyclic loading triplet test is performed on two specimen types. In one type, units are fired solid bricks while in the other they are timber blocks. Joints are composed of earth mortar. Results between the two types are compared, paying attention to friction coefficients and damage patterns. Then, numerical analysis is performed to reproduce a previously performed pull-out test, taking advantage of the results obtained from the triplet test. Though the analysis, frictional behaviour between a timber beam and masonry wall in earth mortar was closely observed in terms of normal and shear stress distributions in the contact surfaces and the deformation of earth mortar. The test showed the contrasts of the frictional performance between brick–mortar and timber-mortar contact surfaces. The analysis suggested that it was effective to physically discretise earth mortar. In this way, frictional behaviour between a timber element and masonry wall was properly reproduced. This paper sheds light on the interaction between timber and brick masonry in earth mortar under lateral loading such as earthquakes.